Conservation of vertebrates and plants in Uganda: Identifying Key Biodiversity Areas and other sites of national importance. Issue 2 (15th April 2019) - Plumptre, Andrew J.; Ayebare, Sam; Behangana, Mathias; Forrest, Tom G.; Hatanga, Paul; Kabuye, Christine; Kirunda, Ben; Kityo, Robert; Mugabe, Hamlet; Namaganda, Mary; Nampindo, Simon; Nangendo, Grace; et al.
Abstract : Uganda is one of the most species rich countries in Africa because of the presence of several major biomes. However, it is also a country that has lost much of its natural habitat to agriculture. Uganda is a country that has been better surveyed for its biodiversity than many African countries, but despite this, there has not been a comprehensive analysis of the critical sites that contribute to biodiversity conservation at a global, as well as at a national level. We here present such an assessment using mammals, birds, reptiles, amphibians, and plants as surrogate taxa. We identified 36 terrestrial sites that are of sufficient global importance to qualify as Key Biodiversity Areas (KBAs), using the Global Standard for the Identification of KBAs, which complement an additional nine freshwater sites. National red listing of species and ecosystems was used to identify sites of national importance for conservation. We employ a conservation planning approach using Marxan to identify the minimum set of sites needed to conserve all the globally and nationally threatened species and nationally threatened habitats in Uganda. The findings show that most of the remaining natural habitat in Uganda is important for the conservation of globally and nationally threatened species and threatened habitat. Large areas of irreplaceable habitat occur outside protected areas, although more extensive surveys of these areas would likely reduce the area that is irreplaceable. Abstract : Priority areas for conservation of both globally and nationally threatened species are identified for the first time in Uganda. Our analysis shows that most natural habitat remaining in the country is critical for the conservation of the rich biodiversity of this country.